Ethnobotanical identification of mango (Mangifera indica L.) and other fruit trees mentioned in Old Javanese Ramayana (10th century Java, Indonesia) - DEDE MULYANTO; BUDIAWATI SUPANGKAT; HARDIAN E. NURSETO; JOHAN ISKANDAR (Society for Indonesian Biodiversity, 2023)
Abstract. Mulyanto D, Supangkat B, Nurseto HE, Iskandar J. 2023. Ethnobotanical identification of mango (Mangifera indica L.) and other fruit trees mentioned in Old Javanese Ramayana (10th century Java, Indonesia). Biodiversitas 24: 609-616. Among the 2778 stanzas in Old Javanese Ramayana (OJR), only 46 (1.6%) mentioned fruit trees. There are 63 Old Javanese phytonyms for fruit or fruit tree and only 12 (19%) of them are Sanskrit in origin. Fifty-six species from 44 genera and 26 families are identified, higher than the number of fruit trees carved in reliefs of Borobudur Temple. Of the 56 species, 13 are exotic, specifically from the Indian subcontinent. One of the exotic trees from India that has been naturalized in Java for centuries is Mangifera indica, which is the most often mentioned in the text. Meanwhile, 39 of them are expressly described as fruits that can be consumed raw as food/dessert. It was also found that there are four landscapes, namely hermitage, countryside, forest, and royal garden, which depict the presence of fruit trees. The forest is the landscape with the most mentioned fruit trees in its description. Furthermore, the fruit tree present in the depiction of all landscapes is Mangifera indica. The prevalence of mango trees in these landscapes is probably related to the mango fruit’s edibility as well as its symbolic and religious significance. Other fruit trees, such as Aegle marmelos, Garcinia xanthochymus, Phyllanthus emblica, and Tamarindus indica also have religious significance in Hinduism.